2003
DOI: 10.2151/jmsj.81.493
|View full text |Cite
|
Sign up to set email alerts
|

Sky Radiometer Measurements of Aerosol Optical Properties over Sapporo, Japan

Abstract: Ground-based sky radiometers were used to measure direct solar irradiance and solar aureole radiance for several years at Sapporo, Tsukuba, and Tokyo, Japan. From these measurements, we computed aerosol optical thickness at 0.5 mm, tð0:5Þ, and the A ˚ ngström exponent, a, and volume size distributions within a column. The optical thickness at Sapporo increased markedly over a short period of time following Asian dust events, and a forest fire in Siberia. The columnar volume size distributions observed during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 47 publications
3
42
0
Order By: Relevance
“…The sky radiometer measured the direct solar irradiance and the distribution of radiances in the aureole region (Aoki and Fujiyoshi, 2003). In the present study, we analyzed a set of measurements of the direct solar irradiance and the solar aureole radiance distributions within 160 • of the center of the Sun.…”
Section: Sky Radiometermentioning
confidence: 99%
“…The sky radiometer measured the direct solar irradiance and the distribution of radiances in the aureole region (Aoki and Fujiyoshi, 2003). In the present study, we analyzed a set of measurements of the direct solar irradiance and the solar aureole radiance distributions within 160 • of the center of the Sun.…”
Section: Sky Radiometermentioning
confidence: 99%
“…Aerosols can also serve as cloud condensation nuclei (CCN) or ice nuclei (IN) (Hansen et al, 1997;Hansen et al, 2000). Aerosol optical properties research is indispensable in the aerosol radiative effect study (Aoki and Fujiyoshi, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted to measure aerosol optical and physical properties (Holben et al, 2001;Takemura et al, 2002;Dubovik et al, 2002;Smirnov et al, 2002;Nakajima et al, 2003;Aoki and Fujiyoshi, 2003;Kim et al, 2004;Eck et al, 2005). Uchiyama et al (2005) studied the characteristics of aeolian dust observed by sky-radiometer at several sites including some in source region.…”
Section: Introductionmentioning
confidence: 99%